2021
DOI: 10.1126/sciadv.abg1969
|View full text |Cite
|
Sign up to set email alerts
|

Restructuring of the plasma membrane upon damage by LC3-associated macropinocytosis

Abstract: The plasma membrane shapes and protects the eukaryotic cell from its surroundings and is crucial for cell life. Although initial repair mechanisms to reseal injured membranes are well established, less is known about how cells restructure damaged membranes in the aftermath to restore homeostasis. Here, we show that cells respond to plasma membrane injury by activating proteins associated with macropinocytosis specifically at the damaged membrane. Subsequent to membrane resealing, cells form large macropinosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 60 publications
1
25
0
1
Order By: Relevance
“…However, our results, showing that inhibition of endocytosis by pitstop2 does not prevent MRGPRX2 targeting to the SGs ( Figure 2C ), strongly suggested that MRGPRX2 can reach the SGs also directly from macropinosomes. Recently, it was demonstrated that cells respond to plasma membrane injury by forming large macropinosomes at the repair site ( 37 ). These structures eventually become positive for the autophagy-related LC3B protein, followed by their shrinkage and fusion with lysosomes ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our results, showing that inhibition of endocytosis by pitstop2 does not prevent MRGPRX2 targeting to the SGs ( Figure 2C ), strongly suggested that MRGPRX2 can reach the SGs also directly from macropinosomes. Recently, it was demonstrated that cells respond to plasma membrane injury by forming large macropinosomes at the repair site ( 37 ). These structures eventually become positive for the autophagy-related LC3B protein, followed by their shrinkage and fusion with lysosomes ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was demonstrated that cells respond to plasma membrane injury by forming large macropinosomes at the repair site ( 37 ). These structures eventually become positive for the autophagy-related LC3B protein, followed by their shrinkage and fusion with lysosomes ( 37 ). Given the lysosomal nature of the MC SGs, the previous reports that documented the presence of LC3 on MC SGs ( 38 , 39 ), and our recent findings on inhibition of MRGPRX2-stimulated secretion by autophagy targeting drugs ( 21 ), we were motivated to examine if LC3 plays a role in MRGPRX2 delivery from macropinosomes to the SGs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular basis for the formation and maturation of macropinocytosis involves multiple signals and pathways. V-ATPases play a crucial role in macropinocytosis by keeping lysosomes acidified [ 113 ]. V-ATPases containing a3 localize to plasma membrane, which is necessary for the distribution of regulatory proteins of macropinocytosis, such as RAC1 [ 114 ].…”
Section: V-atpases In Cancermentioning
confidence: 99%
“…The plasma membrane is by its boundary nature under continuous risk of being damaged by exogenous agents, and conversely is used for programmed permeabilization events associated with cell death pathways. Recent studies [124][125][126] suggest that Atg8ylation-dependent processes and other ATG proteins engaged in non-canonical functions contribute to the protection of plasma membrane against physical damage (modeled by laser damage or detergent treatment), programmed permeabilization by gasderminpores during pyroptosis or MLKL during necroptosis, by MLKL-like permeabilization function of SARS-CoV-2 ORF3a, bacterial pore forming toxins (pneumolysin, lysteriolysin and streptolysin O), and harsh components of the cell walls of microbes such as Mycobacterium tuberculosis [124,126]. Whereas ATG9A engages ESCRT proteins to seal plasma membrane holes immediately upon permeabilization [126], Atg8ylation results in blebbing due to lysosomal exocytosis [124] or endocytic processes termed LC3-associated micropinocytosis which appears to be a Lapoid process [125].…”
Section: Atg8ylation As a Response To Membrane Stress And Damagementioning
confidence: 99%